Sustainable Tourism Development Through The Community-Based "Patju Radja" Concept In West Lombok - Muhamad, Muhamad; Darmawan, Agus (Jurnal Toursci, 2025)
Background. Tourism development is emerging as a prominent initiative in regional advancement. Tourism advancement is anticipated to enhance Regional Original Income and generate employment opportunities in the area. West Lombok Regency is a region with tourism potential. Aim. The notion of "Patju Radja" encompasses a tourism development process aimed at regional transformation towards improvement, involving strategy, execution, and oversight to generate the required added value. It serves as a fundamental basis for the sustainability of the tourism ecosystem, encompassing the potential for the development of the tourism industry. Methods. The methods employed utilize a qualitative descriptive approach to acquire a comprehensive understanding of individual experiences in tourism development about the potential of tourist attractions to implement the "Patju radja" idea. This task involves the collection of both secondary and primary data. Secondary data comprising papers on tourist development plans and initiatives enacted by the West Lombok Regency Government Result. The study results indicate that the notion of "Patju radja" in tourism development can be implemented through a community approach. This strategy underscores the comprehensive engagement of the community in the tourism development process in West Lombok Barat Regency. The "Patju Radja" plan is a community development methodology applicable for constructing a tourism development model in West Lombok Regency, including stakeholders such as the government, private sector, and community. Each performer is anticipated to collaborate in their designated roles and highlight the significance of the broader society. Conclusions. The community approach to tourism development, which prioritizes comprehensive community engagement in the development process, is a crucial technique for fostering community-based tourism under the Patju Radja concept in West Lombok Regency. Implication. Execution. The community development method can facilitate the establishment of a tourism development model in Lombok Barat Regency.